HEATING IN THE LAYER OF DISCRETE MATERIALS - L. E. Rovin; T. M. Zajats (Литьë и металлургия)
The given methods can be used for calculation of heat exchange in the burden heating outfits an d melting units of foundry with fib e r moving of heat carrier.